Pemberdayaan Masyarakat tentang Pencegahan Penggunaan Lem Aibon pada Remaja GKI Syaloom Klademak di Kelurahan Kofkerbu Wilayah Kerja Puskesmas Remu Kota Sorong - Merry Loihala; I Made Raka (Idea Pengabdian Masyarakat, 2021)
Drug abuse, one of which is the use of glue, has been widely used by teenagers. In Indonesia,about 14,000 people out of 70 million teenagers aged 12-21 years have used drugs. The misuse of aibon glue in the West Papua Province is increasingly worrying, with the number of cases approaching 1,000. In Kofkerbu Village,there are about 32 teenagers who often do ngelem and there has never been any activity to deal with teenagers in preventing or eliminating the use of aibon. The results obtained after mentoring with education by PAM GKIYouth Syaloom Klademak there was 12 (38 %). Assistance for children who do glue activities is needed so that behavior changes can occur by stopping the use of aibon glue. This assistance requires the involvement of various elements,     including the     government, religious           leaders  and       health officials.